Understanding Menstruation Material in Fiqh Learning for VII Grade Female Students at SMP Syubbanul Wathon 2 Bandongan Magelang - Fitria Nur Azizah, Dwi; Siswanto, Siswanto (Bulletin of Science Education, 2024)
This research was conducted to determine the factors that influence female students' understanding of menstruation material, how they learn menstrual material, and the extent to which class VII female students understand menstruation material at SMP Syubbanul Wathon 2 Bandongan. This research was conducted at Syubbanul Wathon 2 Bandongan Middle School with a focus on female students' understanding of menstruation material. This research was conducted using qualitative research methods with a descriptive approach and various data analysis, collection and validity techniques to support optimal results. In this research, learning about menstruation material for class VII female students uses several learning stages: learning planning, menstrual learning material, learning methods, learning media, learning evaluation and assessment. The level of understanding of class VII students' material on menstruation at Syubbanul Wathon 2 Middle School is quite good. This can be seen from their interviews and written test results, although some students don't understand it and some of the material is difficult for them. Keywords: Understanding Menstruation Material, Fiqh, Syubbanul Wathon